Floor finishing materials
A multi-layer floor covering with a reinforcing layer of woven or nonwoven fabric impregnated with synthetic resin and polyvinyl chloride resin layers addresses the challenge of rigidity and complexity in aircraft floorings, offering lightweight, easy-to-manufacture, and environmentally friendly solutions.
Patent Information
- Application Number
- JP2021507294
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-15
- Filing Date
- 2020-03-12
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-03-12
AI Technical Summary
Existing floor coverings for vehicles, particularly aircraft, face challenges in achieving sufficient rigidity to withstand impact and deformation while being lightweight and easy to manufacture, with complex manufacturing processes due to multiple laminated resin layers.
A multi-layer floor covering comprising a reinforcing layer made of woven or nonwoven fabric impregnated with a synthetic resin, a base layer and a surface layer made of polyvinyl chloride resin composition, with specific thicknesses and densities to ensure rigidity and flexibility, and optionally including additional reinforcing layers and adhesive layers for enhanced bonding.
The solution provides a lightweight floor covering with appropriate rigidity, easy to manufacture, and reduces the complexity of the production process by minimizing the number of layers, while maintaining flame resistance and reducing smoke and toxic gas emission during combustion.
Smart Images

Figure 0007663493000004 
Figure 0007663493000005 
Figure 0007663493000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a floor covering intended for use as a floor covering in people transport vehicles, such as aircraft. [Background technology]
[0002] For vehicle and aircraft floor coverings, the use of lightweight materials while maintaining good physical properties results in improved fuel economy and reduced operating costs.
[0003] Generally, floor coverings are composed of multiple layers that are combined together. In particular, floor coverings for aircraft require a certain degree of rigidity to limit deformation that may occur during flight and the formation of entrapped air bubbles behind the covering, and therefore can be composed of a reinforcing layer that ensures the rigidity of the product. As such a floor covering, a multi-layer floor covering having two reinforcing layers, a layer of reinforcing fibers and a reinforcing layer made of a thermoplastic polymer such as a polyester resin, an acrylic resin, or a mixture thereof and free of reinforcing fibers, has been disclosed (Patent Document 1).
[0004] However, since this multi-layer floor finishing material is made by laminating multiple resin layers of different types, the manufacturing process is complicated. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2016-163995 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a floor finishing material which has sufficient rigidity to withstand impact and deformation, is lightweight, and can be easily manufactured. [Means for solving the problem]
[0007] The means used in the present invention to solve the above problems are as follows. <1> The present invention comprises a reinforcing layer, a base layer, and a surface layer, the reinforcing layer being made of a woven or nonwoven fabric impregnated with a synthetic resin, the base layer and the surface layer being made of a polyvinyl chloride resin composition, and the reinforcing layer being disposed as the bottom layer. , weight 1000g / m 2 More than 2300g / m 2 Below A multi-layer floor covering comprising a layer A of reinforcing fibres, an adhesive layer B, a backing layer C, a reinforcing layer D free of reinforcing fibres, the reinforcing layer D being made of a thermoplastic polymer selected from the group comprising polyester resins, acrylic resins and mixtures thereof, and a top layer E; a reinforcing composite layer made of polyester reinforced with fibreglass, having a thickness of 540 g / m 2 and a reinforcing composite layer having a thickness of 0.35 mm and an adhesive layer made of thermoplastic polyurethane, 90 g / m 2 and an adhesive layer 0.08 mm thick and two surface layers made of polyvinyl chloride, each 0.55 mm thick and each weighing 655 g / m 2 and a reinforcing composite layer made of polyester reinforced with fiberglass, the surface layer having an areal density of 540 g / m 2 and a reinforcing composite layer of 0.35 mm thickness and 90 g / m 2 and a second reinforcing layer made of thermoplastic polyurethane adhesive having a thickness of 0.08 mm and fiberglass, the second reinforcing layer having a thickness of 220 g / m 2 and a second reinforcing layer having a thickness of 0.20 mm and a second adhesive layer having a thickness of 50 g / m 2 and a second adhesive layer having a thickness of 0.03 mm and two surface layers made of polyvinyl chloride, each having a thickness of 0.50 mm and each having a weight of 570 g / m 2 and a surface layer having an areal density of 100 nm to 150 nm. <2> The bending stiffness measured according to JIS K7106 is 50 MPa or more. <1> A floor finishing material as described in. <3> The base layer and the surface layer contain a plasticizer. <1> or <2> A floor finishing material as described in. <4> The plasticizer is a polyester plasticizer. <3> A floor finishing material as described in. <5> Further, a second reinforcing layer made of a nonwoven fabric or a woven fabric is provided. <1> ~ <4> 13. A floor covering material according to any one of claims 1 to 12. <6> The result of the combustion smoke test (Ds(max)) measured in accordance with ASTM E662 is 200 or less, and the result of the combustion toxic gas test (HCl(ppm)) is 150 or less <1> ~ <5> 13. A floor covering material according to any one of claims 1 to 12. <7> The reinforcing layer is made of a woven fabric impregnated with a synthetic resin. <1> ~ <6> 13. A floor covering material according to any one of claims 1 to 12. <8> The woven fabric is made of glass or carbon. <7> A floor finishing material as described in. <9> The tex of the yarn used in the woven fabric is 30g / 1000m to 300g / 1000m, and the weaving density of the warp yarn and the weft yarn of the woven fabric are 10 / 25mm to 30 / 25mm. <7> or <8> A floor finishing material as described in. <10> The synthetic resin is a thermosetting resin. <1> ~ <9> 13. A floor covering material according to any one of claims 1 to 12. <11> The impregnation amount of the synthetic resin in the reinforcing layer is 20 g / m 2 ~60g / m 2 is <1> ~ <10> 13. A floor covering material according to any one of claims 1 to 12. The present invention relates to the above <1> ~ <11>However, other matters (for example, [1] to
[12] below) are also described below.
[0008] [1] A floor finishing material comprising a reinforcing layer, a base layer, and a surface layer, the reinforcing layer being made of a woven or nonwoven fabric impregnated with a synthetic resin, and the base layer and the surface layer being made of a polyvinyl chloride resin composition. [2] A floor finishing material according to [1], having a bending rigidity of 50 MPa or more measured in accordance with JIS K7106. [3] Weight 1000g / m 2 More than 2300g / m 2 A floor finishing material according to the following [1] or [2]. [4] The floor finishing material according to any one of [1] to [3], wherein the base layer and the surface layer contain a plasticizer. [5] The floor finishing material according to [4], wherein the plasticizer is a polyester-based plasticizer. [6] The floor finishing material according to any one of [1] to [5], further comprising a second reinforcing layer made of a nonwoven fabric or a woven fabric. [7] A floor finishing material according to any one of [1] to [6], having a result of a combustion smoke test (Ds(max)) of 200 or less and a result of a combustion toxic gas test (HCl(ppm)) of 150 or less, measured in accordance with ASTM E662. [8] The floor finishing material according to any one of [1] to [7], wherein the reinforcing layer is made of a woven fabric impregnated with a synthetic resin. [9] The floor covering material according to [8], wherein the woven fabric is made of glass or carbon.
[10] The floor finishing material according to [8] or [9], wherein the tex of the yarn used in the woven fabric is 30 g / 1000 m to 300 g / 1000 m, and the weaving density of the woven fabric is 10 threads / 25 mm to 30 threads / 25 mm.
[11] The floor finishing material according to any one of [1] to
[10] , wherein the synthetic resin is a thermosetting resin.
[12] The impregnation amount of the synthetic resin in the reinforcing layer is 20 g / m 2 ~60g / m 2 The floor finishing material according to any one of [1] to
[11] , Effect of the Invention
[0009] The floor finishing material of the present invention has appropriate rigidity, is lightweight, and does not have a complex layer structure, so that it is possible to provide a floor finishing material that can be easily manufactured.
[0010] Since the resin layer is composed of two layers, a base layer and a surface layer, both of which are made of a polyvinyl chloride resin composition, the number of steps required for production is reduced, making it easy to produce. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view of a floor covering according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a floor covering according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention relates to a floor finishing material that includes at least a reinforcing layer, a base layer, and a surface layer. The reinforcing layer, the base layer, and the surface layer are laminated together to form the floor finishing material.
[0013] The floor finishing material of the present invention is characterized by being lightweight and having appropriate rigidity, and is suitable as a floor finishing material for vehicles such as aircraft. For floor finishing materials for such applications, other considerations are also given to flame resistance, reduction in the amount of smoke and toxic gases generated during combustion, etc.
[0014] Each component of the floor finishing material of the present invention will be described. FIG. 1 shows one embodiment of the floor covering material of the present invention.
[0015] The reinforcing layer 1 is made of a composite material consisting of a woven or nonwoven fabric and a thermosetting or thermoplastic synthetic resin. The reinforcing layer 1 is made of a woven or nonwoven fabric impregnated with the synthetic resin, and provides sufficient rigidity to the floor finishing material.
[0016] The woven or nonwoven fabric of the reinforcing layer 1 is made of inorganic or organic natural or synthetic fibers. Desirably, the fibers are selected from the group including glass, carbon, aramid, polyethylene, zylon, nylon, polyester, acrylic, vinylon, linen, cotton, hemp, etc. Among them, glass and carbon are more preferable.
[0017] The synthetic resin of the reinforcing layer 1 may be a thermosetting or thermoplastic synthetic resin selected from the group including polyester resin, phenol resin, epoxy resin, polysulfone resin, vinyl ester resin, acrylic resin, polyamide resin, polycarbonate resin, and mixtures thereof. Among them, a thermosetting resin is preferable, and an unsaturated polyester resin, a phenol resin, an epoxy resin, etc. are more preferable.
[0018] The thickness of the reinforcing layer 1 is preferably 0.2 mm to 0.4 mm. By making it 0.2 mm or more, sufficient bending rigidity can be obtained, and by making it 0.4 mm or less, it becomes easier to suppress an increase in manufacturing difficulty due to an increase in weight and a decrease in flexibility. In addition, the weight of the reinforcing layer 1 is 200 g / m 2 From 400 g / m 2 Up to is preferred.
[0019] The reinforcing layer 1 is preferably disposed at the bottom layer of the floor finishing material, as in the floor finishing material A (floor finishing material A1) in Fig. 1. When the floor finishing material A is laid on the floor of an aircraft, the reinforcing layer is attached to the floor structure of the aircraft body with an adhesive or adhesive.
[0020] The reinforcing layer 1 is made of a composite material comprising a woven or nonwoven fabric and a thermosetting or thermoplastic synthetic resin, and is not particularly limited as long as the woven or nonwoven fabric is impregnated with the synthetic resin and is in a solidified state, but a woven fabric is preferably used because it has a moderate mesh size and is also excellent in strength. By making the mesh size in the composite material not too small but moderate, the reinforcing layer 1 can be made lighter and the weight of the floor finishing material A can be prevented from increasing. In addition, since the material can be given a moderate flexibility, the manufacturing process of the floor finishing material A is less likely to be restricted. The reinforcing layer 1 is preferably made of a woven fabric impregnated with a synthetic resin. The woven fabric is preferably made of glass or carbon. The woven fabric is not particularly limited, but is preferably a plain weave.
[0021] Here, the mesh size of the woven fabric depends on the tex of the yarn used in the woven fabric, the weaving density, which is the number of threads per unit length (25 mm), and the amount of synthetic resin used. The tex of the yarn used in the woven fabric is preferably 30 g / 1000 m to 300 g / 1000 m, more preferably 50 g / 1000 m to 200 g / 1000 m, and even more preferably 100 g / 1000 m to 150 g / 1000 m. The weaving density, which is the number of threads per unit length (25 mm), is preferably 10 threads / 25 mm to 30 threads / 25 mm, and more preferably 15 threads / 25 mm to 25 threads / 25 mm. When the weaving density of the warp and weft threads of the woven fabric is different, it is preferable that both the weaving density of the warp threads and the weft threads are in the above range.
[0022] It is preferable that the tex of the yarn used in the woven fabric is 30 g / 1000 m to 300 g / 1000 m, and the weaving density of the woven fabric is 10 threads / 25 mm to 30 threads / 25 mm. In addition, since the amount of impregnation of the synthetic resin also affects the flexibility and weight of the floor finishing material A, the amount of impregnation of the synthetic resin in the reinforcing layer 1 is set to 20 g / m 2 From 60 g / m 2 is preferably 30 g / m 2 From 50g / m 2 is more preferred.
[0023] The base layer 2 and the surface layer 3 are made of a polyvinyl chloride resin composition. Among general thermoplastic resins, polyvinyl chloride resins are flame retardant and are suitable as materials for vehicle floor finishing materials. The polyvinyl chloride resin compositions constituting the base layer 2 and the surface layer 3 may contain a plasticizer to impart appropriate flexibility.
[0024] Examples of polyvinyl chloride resins used in the polyvinyl chloride resin composition include polyvinyl chloride homopolymer resins, polychlorinated vinyl chloride resins, polyvinyl chloride copolymer resins (e.g., vinyl acetate-vinyl chloride copolymers, ethylene-vinyl chloride copolymers, etc.), vinyl chloride graft copolymers (e.g., ethylene-vinyl acetate-vinyl chloride graft copolymers, polyurethane-vinyl chloride graft copolymers, etc.), and the like. These can be used alone or in combination of two or more kinds.
[0025] Examples of the plasticizer used in the polyvinyl chloride resin composition include phthalate plasticizers, polyester plasticizers, sulfonate plasticizers, phosphate plasticizers, adipate plasticizers, epoxy plasticizers, etc. Among these, polyester plasticizers are preferred, and the amount of smoke generated during combustion can be reduced by using a polyester plasticizer, which is a polycondensate of an aliphatic dibasic acid and a diol. Examples of the aliphatic dibasic acid of the polyester plasticizer include succinic acid, maleic acid, fumaric acid, glutamic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, etc. Examples of the diol include 1,2-propylene glycol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2,2-diethyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl-1,8-octanediol, 1,12-octadecanediol, etc. Among them, adipic acid-based polyester plasticizers are preferably used because they have excellent plasticizing efficiency and produce little smoke during combustion.
[0026] The preferred amount of these plasticizers added is 15 to 75 parts by weight, more preferably 25 to 65 parts by weight, for the base layer 2, relative to 100 parts by weight of the polyvinyl chloride resin, and 10 to 60 parts by weight, more preferably 20 to 50 parts by weight, for the surface layer 3, relative to 100 parts by weight of the polyvinyl chloride resin.
[0027] In addition to the plasticizer, an inorganic filler and a flame retardant can be added to the polyvinyl chloride resin composition of the base layer 2 .
[0028] Examples of fillers used in the polyvinyl chloride resin composition of the base layer 2 include carbonates such as calcium carbonate and magnesium carbonate, layered silicates such as clay, talc, and mica, and hollow balloons such as fly ash balloons, shirasu balloons, and glass balloons. Addition of a filler improves dimensional stability and heat resistance, reduces the amount of smoke generated during combustion and the amount of toxic gases such as HCl, and reduces costs. In particular, it is preferable to add calcium carbonate because it is highly effective in reducing the amount of toxic gases during combustion and reducing costs.
[0029] The amount of these fillers added is preferably 5 to 100 parts by weight, and more preferably 25 to 80 parts by weight, based on 100 parts by weight of the polyvinyl chloride resin.
[0030] Examples of flame retardants used in the polyvinyl chloride resin composition of the base layer 2 include inorganic materials such as molybdic acid compounds, zinc stannate compounds, nitrogen-based compounds such as ammonium carbonate and boron nitride, metal hydroxides such as magnesium hydroxide and aluminum hydroxide, and antimony-based compounds such as antimony oxide, and organic materials such as halogen-based compounds such as bromine-based compounds and phosphorus-based compounds such as phosphate esters. The use of a flame retardant improves flame retardancy and reduces the amount of smoke generated during combustion and the amount of toxic gases such as HCl. In particular, it is preferable to use molybdic acid compounds and zinc stannate compounds because they are highly effective in reducing the amount of smoke generated during combustion.
[0031] The amount of these flame retardants added is 5 to 100 parts by weight, preferably 25 to 80 parts by weight, based on 100 parts by weight of the polyvinyl chloride resin.
[0032] The thickness of the base layer 2 is preferably from 0.5 mm to 1.1 mm, more preferably from 0.6 mm to 1.0 mm. The weight of the base layer 2 is 700 g / m 2 from 1550g / m 2 Up to 800 g / m 2 From 1450g / m 2 Up to is more preferable.
[0033] The surface layer 3 is disposed on the uppermost surface of the floor finishing material, and the upper surface of the surface layer 3 (the surface opposite to the base layer 2) will be exposed on the floor surface after construction. For this reason, it is desirable to add various pigments to the polyvinyl chloride resin composition of the surface layer 3 to color it, or to impart design features to the surface by providing irregularities by embossing or the like.
[0034] Furthermore, by imparting transparency to the surface layer 3 and printing patterns or decorations on the underside of the surface layer 3 (the surface facing the base layer 2) or the upper surface of the base layer 2 (the surface facing the surface layer 3), a floor finishing material can be made that has excellent design and can protect the design from wear of the surface layer 3 that can occur when the material is applied to a floor surface and used.
[0035] Furthermore, if the resins of the layer on which the design is printed (in this case, base layer 2) and surface layer 3 are different, the material used for printing must have good adhesion to both resins; otherwise, the peel strength will decrease, requiring the use of a primer or the materials used for printing will be limited. However, if the resins used for both layers are the same, the range of materials available for printing is greatly increased.
[0036] The thickness of the surface layer 3 is preferably 0.1 mm to 0.3 mm. The weight of the surface layer 3 is 100 g / m 2 from 350 g / m 2 Up to is preferred.
[0037] The polyvinyl chloride resin compositions of the base layer 2 and the surface layer 3 may contain stabilizers, lubricants, UV absorbers, pigments, light stabilizers, antioxidants, antibacterial agents, foaming agents, fillers, etc., as required.
[0038] The thickness of the floor covering is preferably from 0.8 to 1.8 mm, more preferably from 1.0 to 1.8 mm. The weight of the floor covering is 1000 g / m 2 From 2300g / m 2 Up to 1250 g / m 2 From 2300g / m 2 Up to is more preferable.
[0039] The floor finishing material preferably has a bending stiffness of 50 MPa or more, more preferably 100 MPa or more, measured according to JIS K7106. By making it 50 MPa or more, sufficient bending stiffness is obtained, and in floor finishing materials for aircraft, deformation that may occur during flight and formation of air bubbles on the back of the finishing material are easily suppressed. In addition, if the bending stiffness is 500 MPa or less, when it is made into a long floor finishing material, it can be wound around a paper tube or the like and stored and transported in a roll shape, which makes it easy to handle during construction, and is more preferably 400 MPa or less.
[0040] In addition, since it is difficult to evacuate vehicles and aircraft if a fire breaks out during operation, it is desirable for them to be flame retardant and to reduce the amount of smoke and toxic gases emitted during combustion. The same is true for floor finishing materials, and in terms of specific performance, it is preferable that the amount of smoke emitted during flaming and non-flaming combustion and the concentration of toxic gases (hydrogen chloride gas) are both within the following ranges in accordance with the test method specified in ASTM E662. The amount of smoke (Ds(max)) is preferably 200 or less, more preferably 150 or less. The toxic gas (hydrogen chloride gas) concentration (HCl(ppm)) is preferably 150 ppm or less, more preferably 100 ppm or less.
[0041] In addition to the reinforcing layer 1, base material layer 2, and surface layer 3, an adhesive layer 4 and a second reinforcing layer 5 may be provided. For example, as in the floor finishing material A (floor finishing material A2) in Fig. 2, a structure of a surface layer 3, a base material layer 2, a second reinforcing layer 5, a base material layer 2', an adhesive layer 4, and a reinforcing layer 1 may be used. Fig. 2 shows another embodiment of the floor finishing material of the present invention.
[0042] The adhesive layer 4 has the effect of increasing the bonding strength between the reinforcing layer 1 and the base layer 2. Methods for bonding the reinforcing layer 1 and the base layer 2 include a method of laminating each layer and then heating it, a method of heating each layer and then embossing while laminating them (laminate embossing), and a method of laminating the reinforcing layer 1 on the base layer 2 in a molten state on a production line when forming the base layer 2 into a sheet. However, if the synthetic resin used in the reinforcing layer 1 is not compatible with the polyvinyl chloride resin of the base layer 2, an adhesive layer 4 compatible with each layer can be provided between the reinforcing layer 1 and the base layer 2 to prevent peeling between the reinforcing layer 1 and the base layer 2.
[0043] The adhesive layer 4 is preferably a polymer selected from the group including copolymer polyamide, vinyl chloride copolymer, thermoplastic polyurethane, ethylene vinyl acetate, copolymer polyester, and mixtures thereof. For example, when the synthetic resin used in the reinforcing layer 1 is a phenolic resin, an adhesive layer 4 made of a vinyl chloride copolymer can be suitably used. The amount of the adhesive 4 applied is not particularly limited, but is preferably 3 g / m 2From 250 g / m 2 Up to is preferred.
[0044] The bending rigidity and dimensional stability can be improved by further providing the second reinforcing layer 5. The second reinforcing layer 5 is a woven or nonwoven fabric, and is made of inorganic or organic natural or synthetic fibers. Desirable examples of the fibers include those selected from the group including glass, carbon, aramid, nylon, polyester, acrylic, vinylon, linen, cotton, and hemp. Among these, glass and carbon are more preferable. The thickness of the second reinforcing layer 5 is not particularly limited, but is preferably from 0.03 mm to 0.5 mm. Furthermore, for example, when a woven fabric is used as the second reinforcing layer 5, in a floor finishing material formed by laminating the second reinforcing layer 5 on the base material layer 2' as shown in Figure 2, the second reinforcing layer 5 is incorporated into the base material layer 2'.
[0045] In the floor finishing material, each of the base layer 2 and the surface layer 3 is obtained by mixing the respective prescribed materials and molding them with a molding machine such as an extruder or a calendar. The floor finishing material can be obtained by laminating each of these layers and the reinforcing layer 1, together with the adhesive layer 4 provided on the reinforcing layer 1 as necessary, and then heat treating the laminate. Alternatively, the floor finishing material can be obtained by molding each layer at once and laminating them together using a multi-layer extruder.
[0046] The adhesive layer 4 can be produced by applying the adhesive to the reinforcing layer 1 by dipping, bar coating, gravure coating, reverse coating, die coating or the like, and then subjecting the layer to a heat treatment in a drying oven or the like.
[0047] Furthermore, a floor finishing material can be obtained through a process of printing a design, imparting a grain to the surface layer, and applying pressure after heating for laminating each layer.
[0048] The second reinforcing layer 5 may be disposed between the multiple base layers 2, 2' as shown in FIG. 2, or between the base layer 2 and the surface layer 3. However, it is preferable that the second reinforcing layer 5 is disposed between the multiple base layers 2, 2' so that the surface unevenness of the second reinforcing layer 5 is less likely to affect the surface of the surface layer 3 (the surface opposite to the base layer 2). When the second reinforcing layer 5 is provided, the second reinforcing layer 5 is disposed at a desired position, such as between the base layers 2, 2', and a heat treatment or the like is performed to obtain a floor finishing material. Alternatively, each layer may be molded at once using a multilayer extruder and laminated. After that, the floor finishing material can be obtained through the above-mentioned heating and pressurizing process.
[0049] Just as an adhesive layer 4 may be provided to improve adhesion between the reinforcing layer 1 and the base layer 2, an adhesive layer may also be provided between the second reinforcing layer 5 and other layers if necessary; however, if the adhesion between the second reinforcing layer 5 and other layers is sufficient, it will be easier to manufacture the product if these layers are not applied. EXAMPLES
[0050] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.
[0051] The materials used in the examples and comparative examples are as follows. Polyvinyl chloride resin: Polyvinyl chloride, degree of polymerization 1000 Phthalate plasticizer: DOP (dioctyl phthalate) Polyester plasticizer: Adipic acid polyester plasticizer Viscosity (25°C) 150mPa·s Phosphate plasticizer: TCP (tricresyl phosphate) Stabilizer: Barium zinc stabilizer Filler: Precipitated calcium carbonate Flame retardant: Mixture of zinc hydroxystannate and molybdic acid compounds (mixture ratio 3:2 (by weight)) Backing: Woven polyester fabric Adhesive: Vinyl chloride copolymer (vinyl chloride-vinyl acetate copolymer) emulsion
[0052] The reinforcing layers in Examples 1, 2 and 6 and Comparative Examples 1 to 5 are as follows. Reinforcement layer: Phenolic resin impregnated glass woven fabric (plain weave) thickness 0.3 mm Yarn used: Tex 135 (g / 1000m) Weave density: warp 19 / 25mm, weft 21 / 25mm Resin impregnation amount: 40g / m 2
[0053] The second reinforcing layer in Example 6 is as follows. Second reinforcing layer: Glass woven fabric (leno weave) thickness 0.1 mm Thread used: Tex warp thread 34 (g / 1000m) · weft thread 69 (g / 1000m) Weaving density: warp 10 x 2 / 25mm, weft 10 / 25mm
[0054] Examples 1 and 6, Comparative Examples 1 to 3 <Sheet manufacturing method> The compositions of the surface layer and the base layer were mixed based on the composition in Table 1, and the obtained compounds were used to prepare sheets of each layer using two rolls at 175 ° C. In addition, one side of the reinforcing layer used in the examples was coated with an adhesive by bar coating, and then heated and dried at 140 ° C for 30 seconds to form an adhesive layer. Then, the obtained layers were laminated and pressed at 170 ° C to obtain the floor finishing material shown in Table 1. Here, the one having the backing material was laminated in the order of backing material / base layer / surface layer from the bottom, and the one having the reinforcing layer was laminated in the order of reinforcing layer / adhesive layer / base layer / surface layer from the bottom. The one having the second reinforcing layer was laminated in the order of reinforcing layer / adhesive layer / base layer (bottom) / second reinforcing layer / base layer (top) / surface layer from the bottom.
[0055] <Weight measurement> In this specification, the weight is measured by measuring the weight of a 10 cm square sample using an electronic balance and converting the obtained value into 1 m 2 The weight per unit was calculated (g / m 2 ).
[0056] <Measurement of bending stiffness> The bending stiffness in this specification was measured in accordance with the test method specified in JIS K 7106. Specifically, one end of the floor finishing material was fixed to a chuck, and when it was bent to a specified bending angle, the bending stiffness was calculated from the bending moment applied to the other end and the bending angle.
[0057] [Table 1]
[0058] As is clear from Table 1, in Examples 1 and 6, the floor finishing material is thinner than Comparative Examples 1 to 3, which do not have a reinforcing layer, but the flexural rigidity is large and sufficient rigidity is obtained. If the floor finishing material is thicker as in Comparative Examples 1 and 2, the weight increases and is not preferable. In Comparative Example 2, polyester woven fabric is used as the backing material instead of the reinforcing layer, but no significant improvement in the flexural rigidity is observed. Furthermore, it was confirmed that there is a significant difference in the flexural rigidity depending on whether or not there is a reinforcing layer (in this example, phenolic resin-impregnated glass woven fabric).
[0059] Example 2, Comparative Examples 4 and 5 <Sheet manufacturing method> The surface layer and base layer compositions were mixed based on the composition in Table 2, and the resulting compounds were used to prepare sheets for each layer using two rolls at 175°C. In addition, one side of the reinforcing layer used in the examples was coated with an adhesive by bar coating, and then heated and dried at 140°C for 30 seconds to form an adhesive layer. The resulting layers were then laminated and pressed at 170°C to obtain the floor finishing material shown in Table 2. Here, the reinforcing layer was laminated in the order of reinforcing layer / adhesive layer / base layer / surface layer from the bottom.
[0060] <Measurement of smoke generation> The amount of smoke generated in this specification was measured in flaming and non-flaming combustion according to the test method specified in ASTM E662. Specifically, a sample was placed in a sealed chamber and burned for 4 minutes using an electric heater and a gas burner (flaming combustion only). The extinction coefficient was calculated from the intensity of the light transmitted by the phototube during combustion, and the specific optical density at the maximum value of the extinction coefficient was calculated, and the amount of smoke generated was calculated based on this value (Ds(max)).
[0061] <Measurement of hydrogen chloride gas amount> The amount of hydrogen chloride gas in this specification was measured in accordance with the test method specified in ASTM E662, and the amount of smoke generated during flaming and non-flaming combustion was measured. Specifically, a sample was placed in a sealed chamber and burned for 4 minutes using an electric heater and a gas burner (flaming combustion only). At the end of the test, 100cc of air in the chamber was ventilated into the detector tube to measure the concentration of the toxic gas (hydrogen chloride gas) (HCl (ppm)).
[0062] [Table 2]
[0063] As is clear from Table 2, it was confirmed that the amount of smoke generated and the amount of hydrogen chloride gas can be significantly reduced by using polyester-based plasticizers, phosphate-based plasticizers, and flame retardants, and that the use of a reinforcing layer has almost no effect on the amount of smoke generated and the amount of hydrogen chloride gas.
[0064] Examples 3 to 5 <Sheet manufacturing method> A sheet was produced in the same manner as in Example 2, except that the following reinforcing layers (1) to (3) having different weaving densities were used as the reinforcing layers. Reinforcing layers (1) to (3): Phenolic resin-impregnated glass woven fabric (plain weave) thickness 0.3 mm Yarn used: Tex 135 (g / 1000m) (1)~(3) Weaving density (1) Warp threads 19 / 25mm, weft threads 18 / 25mm (2) Warp threads 19 / 25mm, weft threads 21 / 25mm (3) Warp threads 25 / 25mm, weft threads 25 / 25mm Resin impregnation amount: 40g / m 2 Common to (1) to (3)
[0065] <Measurement of peel strength in 90° peel test> The reinforcing layer is peeled off from the base layer at one end of a sheet sample having a width of 25 mm and a length of 200 mm to prepare a gripping portion of the reinforcing layer having a length of 50 mm. The obtained sheet sample was fixed to a jig for a 90° peel test of a Shopper-type tensile testing machine (Model: TS-1563, manufactured by Ueshima Seisakusho) under standard conditions (23±2°C, relative humidity 50±10%), the gripping portion of the aforementioned reinforcing layer was clamped with a chuck, and the sheet was pulled with a load capacity of 100 N and a pulling speed of 200 mm / min to measure the peel strength.
[0066] <Measurement of flexibility> The flexibility in this specification was measured in accordance with the flexibility test method specified in JIS A1454. Specifically, under standard conditions (23±2°C, relative humidity 50±10%), the floor finishing material was wound around mandrels with diameters of Φ100mm, 90mm, 80mm, 70mm, 60mm, 50mm, 40mm, and 30mm in order with the reinforcing layer facing inward, and then bent to check whether cracks in the reinforcing layer or peeling from the base layer occurred. The values in Table 3 indicate the minimum diameter at which cracks or peeling do not occur.
[0067] [Table 3]
[0068] In the 90° peel test, the reinforcing layer of Example 3 broke before peeling occurred between the reinforcing layer and the base layer, but the interlayer strength was sufficient. In Examples 4 and 5, the reinforcing layer and the base layer peeled off without breaking, and the peel strength between the reinforcing layer and the base layer was 60N / 25mm and 45N / 25mm, respectively, so that the strength of the reinforcing layer and the interlayer strength were sufficient. In addition, in the measurement of flexibility, cracks occurred in the reinforcing layer of Example 5 when it was wound around a mandrel with a diameter of Φ60mm. In Examples 3 and 4, cracks and peeling did not occur in the reinforcing layer even with a mandrel with a diameter of Φ30mm, and the flexibility was excellent. In this way, it was confirmed that the strength and flexibility of the floor finishing material differed depending on the degree of weaving density (opening) of the reinforcing layer. [Industrial Applicability]
[0069] According to the present invention, it is possible to provide a floor finishing material that has sufficient rigidity to withstand impact and deformation, is lightweight, and can be easily manufactured.
[0070] Although the present invention has been described in detail and with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made therein without departing from the spirit and scope of the invention. This application is based on a Japanese patent application (Patent Application No. 2019-048289) filed on March 15, 2019, the contents of which are incorporated herein by reference. [Explanation of symbols]
[0071] A Floor finishing material 1 Reinforcement layer 2, 2´ base material layer 3 Surface layer 4 Adhesive layer 5 Second reinforcement layer
Claims
1. A floor finishing material comprising a reinforcing layer, a base layer and a surface layer, the reinforcing layer being made of a woven or nonwoven fabric impregnated with a synthetic resin, the base layer and the surface layer being made of a polyvinyl chloride resin composition, the reinforcing layer being arranged as the bottom layer, and having a weight of 1000 g / m 2 or more and 2300 g / m 2 or less (however, the following is not included in the floor finishing material: a multi-layer floor finishing material comprising a layer A of reinforcing fibers, an adhesive layer B, a back layer C, a reinforcing layer D free of reinforcing fibers, the reinforcing layer D being made of a thermoplastic polymer selected from the group including polyester resin, acrylic resin and mixtures thereof, and a surface layer E; a reinforcing composite layer made of polyester reinforced with fiberglass, the weight of which is 540 g / m 2 or more and 2300 g / m 2 or less; 2 and a reinforcing composite layer having a thickness of 0.35 mm and an adhesive layer made of thermoplastic polyurethane, 90 g / m 2 and an adhesive layer having a thickness of 0.08 mm and two surface layers made of polyvinyl chloride, each having a thickness of 0.55 mm and each having a weight of 655 g / m 2 and a reinforcing composite layer made of polyester reinforced with fiberglass, the surface layer having an areal density of 540 g / m. 2 and a reinforcing composite layer having a thickness of 0.35 mm and a thickness of 90 g / m 2 and a second reinforcing layer made of a thermoplastic polyurethane adhesive having a thickness of 0.08 mm and fiberglass, the second reinforcing layer having a thickness of 220 g / m 2 and a second reinforcing layer having a thickness of 0.20 mm and a second adhesive layer having a thickness of 50 g / m 2 and a second adhesive layer having a thickness of 0.03 mm and two surface layers made of polyvinyl chloride, each having a thickness of 0.50 mm and each having a weight of 570 g / m 2 and a surface layer having an areal density of 100 nm to 150 nm.
2. 2. The floor finishing material according to claim 1, which has a bending stiffness of 50 MPa or more as measured in accordance with JIS K7106.
3. 3. The floor finishing material according to claim 1, wherein the base layer and the surface layer contain a plasticizer.
4. 4. The floor covering of claim 3, wherein the plasticizer is a polyester plasticizer.
5. The floor covering material according to any one of claims 1 to 4, further comprising a second reinforcing layer made of a nonwoven fabric or a woven fabric.
6. 6. The floor covering material according to any one of claims 1 to 5, which has a result of a combustion smoke test (Ds(max)) of 200 or less and a result of a combustion toxic gas test (HCl(ppm)) of 150 or less, measured in accordance with ASTM E662.
7. The floor finishing material according to any one of claims 1 to 6, wherein the reinforcing layer is made of a woven fabric impregnated with a synthetic resin.
8. 8. The floor covering of claim 7, wherein the woven fabric is made of glass or carbon.
9. 9. The floor finishing material according to claim 7 or 8, wherein the tex of the yarn used in the woven fabric is 30 g / 1000 m to 300 g / 1000 m, and the weaving density of the warp yarns and the weft yarns of the woven fabric are 10 threads / 25 mm to 30 threads / 25 mm.
10. The floor finishing material according to any one of claims 1 to 9, wherein the synthetic resin is a thermosetting resin.
11. The impregnation amount of the synthetic resin in the reinforcing layer is 20 g / m 2 ~60g / m 2 The floor finishing material according to any one of claims 1 to 10,
Citation Information
Patent Citations
Multilayer fabric materials for roofing applications
EP2309046A1
Floor material and manufacture thereof
JP1993163824A
Long floor member
JP2001323646A
Abrasion resistant laminate and manufacturing method thereof
JP2001519256A
Low smoke polyvinyl chloride-based sheet
JP2013189607A